Analysis of BNT162b2‐ and CVnCoV‐elicited sera and of convalescent sera toward SARS‐CoV‐2 viruses. Issue 7 (2nd December 2021) - Hein, Sascha; Herrlein, Marie‐Luise; Mhedhbi, Ines; Bender, Daniela; Haberger, Vanessa; Benz, Nuka; Eisert, Jonathan; Stingl, Julia; Dreher, Michael; Oberle, Doris; Schulze, Jessica; Mache, Christin; et al.
Summary: Background: The mRNA vaccine BNT162b2 (Comirnaty, BioNTech/Pfizer) and the vaccine candidate CVnCoV (Curevac) each encode a stabilized spike protein of SARS‐CoV2 as antigen but differ with respect to the nature of the mRNA (modified versus unmodified nucleotides) and the mRNA amount (30 μg versus 12 μg RNA). This study characterizes antisera elicited by these two vaccines in comparison to convalescent sera. Methods: Sera from BNT162b2 vaccinated healthcare workers, and sera from participants of a phase I trial vaccinated with 2, 4, 6, 8, or 12 μg CVnCoV and convalescent sera from hospitalized patients were analyzed by ELISA, neutralization tests, surface plasmon resonance (SPR), and peptide arrays. Results: BNT162b2‐elicited sera and convalescent sera have a higher titer of spike‐RBD‐specific antibodies and neutralizing antibodies as compared to the CVnCoV‐elicited sera. For all analyzed sera a reduction in binding and neutralizing antibodies was found for the lineage B.1.351 variant of concern. SPR analyses revealed that the CVnCoV‐elicited sera have a lower fraction of slow‐dissociating antibodies. Accordingly, the CVnCoV sera almost fail to compete with the spike‐ACE2 interaction. The significance of common VOC mutations K417N, E484K, or N501Y focused on linear epitopes was analyzed using a peptide array approach. The peptide arrays showed a strong difference between convalescent sera and vaccine‐elicited sera. Specifically, the linear epitope at position N501 was affected by the mutation and elucidates the escape of viral variants to antibodies against this linear epitope. Conclusion: These data reveal differences in titer, neutralizing capacity, and affinity of the antibodies between BNT162b2‐ and CVnCoV‐elicited sera, which could contribute to the apparent differences in vaccine efficacy. Abstract : This study presents comparative characterization of differences between sera derived from BNT162b‐ or CVnCoV‐vaccinated individuals and first‐wave convalescent patients. In addition to standard titer measurements, we used novel methods for sera analysis, such as SPR to measure antibody‐antigen complexes and SARS‐CoV‐2 variant‐specific peptide arrays to study efficiency against linear epitopes. Our results indicate a strong difference between all three serum groups (also between the two vaccine types), especially with respect to the titer, affinity, and binding pattern to linear epitopes of the elicited antibodies.Abbreviations: Ab, antibody; Alpha, SARS‐CoV‐2 Alpha variant; Beta, SARS‐CoV‐2 Beta variant; BNT162b2, mRNA COVID‐19 vaccine; COVID‐19, coronavirus disease 2019; Ctrl, negative control sera; CVnCoV, mRNA COVID‐19 vaccine; mRNA, messenger ribonucleic acid; RBD, receptor‐binding domain; SARS‐CoV‐2, severe acute respiratory syndrome coronavirus 2